Python Django dev to deployment - Traversy, Brad (Packt Publishing, 2019)
"This is a very practical course where we take a list of requirements from a fictional company to build a real estate application using Django. We will take a basic html/css Bootstrap 4 theme and turn it into a real working application with an admin area to manage resources including property listings, realtors and contact inquiries. We also have a section on learning basic Python syntax."--Resource description page